Digitalizing Nigerian University Learning System: How Ready Are the Students? - Chinenye Amaonye; Adaora Vivian Anyaeji (Journal of Digital Learning and Education, 2023)
The Nigerian higher education has been plugged into a huge gap between the demand for higher education and the shortage in supply as a result of its inability to absorb the increasing number of students which has been exasperated by the persisted industrial actions by the university lecturers, insecurity, associated effects of post Covid 19 pandemic, among others, thereby hindering access to the teeming population of admission seeking individuals to universities. To this end, the study investigated the online readiness of students towards digitalization of university learning system with 333 out of 2000 undergraduate students in public universities. Three research questions guided while Students’ Readiness for Online University Learning Scale (SROULS) instrument was developed for this study. The results indicate high level of readiness of students towards digitalization of university learning with overall mean of the construct at 3.73. Also, the percentage level of online readiness of female student insignificantly differs from the male students. Challenges affecting digitization of university learning system were identified. Therefore, it recommended legalization of online university system and provision of enabling environment for its successful implementation in Nigerian education; improved power stability, internet connectivity among others.